Resenha de: Economic Systems and Society - Megale, Januário Francisco (Revista de História, 1975)
DALTON  (George). — Economic Systems and Society. Capitalism, Communismand the Third World.  Harmondworth (Inglaterra), PenguinBooks, 1974, 250 pp.